Status of RF system for VEPP-5 damping ring - Gusev, Ye.; Kot, N.; Krutikhin, S.; Kuptsov, I.; Kurkin, G.; Makarov, I.; Matyash, N.; Mironenko, L.; Motygin, S.; Osipov, V.; Ostreiko, G.; Petrov, V.; et al. (Вопросы атомной науки и техники, 2006)
The paper presents the RF system of VEPP-5 damping ring created at BINP Novosibirsk. The RF system operates at 700 MHz and consists of the generator based on KU-393 klystron, transmitting waveguide with wave-to-coax adapters, accelerating cavity, and control system. HOM cavities are damped with resistive loads to eliminate the beam instability. Parameters and results of cold measurement tests and high power level tests are presented.